The Sahel conflict: Economic & security spillovers on West Africa - Sherillyn Raga; Alberto Lemma; Jodie Keane (Overseas Development Institute (ODI), 2023)
Extremist activities and violence in the centres of conflict in the Sahel (i.e. Burkina Faso, Mali and Niger) are moving south towards the four countries of interest of this paper (Côte d'Ivoire, Ghana, Senegal and Togo). At the time of writing, all except Ghana have experienced direct jihadist attacks, and all have reported extremist encroachment and recent increases in refugees, especially from Burkina Faso. The Sahel conflict may affect economic performance in the focus countries in two ways. One pathway is through economic spillover effects. Even though the epicentre of extremist attacks and humanitarian disaster is in Mali, Niger and Burkina Faso, impacts on focus countries may be transmitted through economic links (e.g. trade, investment, remittances) with conflict-affected countries, and their policy response (e.g. refugee management, security defence, trading partner substitution). These effects are already happening. Losses through lower exports and FDI flows could be equivalent to between 1.3% (Ghana) and nearly 5% (Senegal) of GDP. Another pathway is through 'conflict spillovers', whereby conflict and violence from the centre of the Sahel are transmitted to the focus countries. This pathway would lead to adverse effects on lives and economic activities and may result in an 8% reduction in GDP in the focus countries at the onset of an intense conflict. In both pathways, higher military spending involved in mitigating the effects (of both conflict and economic spillovers) in the four countries would add further pressure to their macro-financial stability risks, given that they are currently dealing with high inflation and moderate/high risk of debt distress (Ghana is already in default). Economic spillover effects of the conflict may be mitigated by ensuring that trade, FDI and financial channels in the Sahel region are open, safe and facilitated. It is critical to continue combatting the spread of extremism, while simultaneously addressing the structural roots of extremism. Evidence suggests that deepening trade and investment reduces disputes, while MSME-led development improves social cohesion. Political ownership, stronger fiscal positions, and predictable and patient financing for multi-stakeholder and conflict-sensitive interventions may help the Sahel region achieve economic resilience and better peace outcomes.
Keywords: 330; Western Sahara; Ghana; Africa; Conflict; Ivory Coast; Togo; Trade & investment; Niger; Senegal; Burkina Faso; Mali; Economics